A General Approach to Modeling Covid-19 - Isea, Raul (Journal of Model Based Research, 2023)
The present work shows that it is possible to analytically solve a general model to explain the transmission dynamics of SARS-CoV-2. First, the within-host model is described, and later a between-host model, where the coupling between them is the viral load of SARS-CoV-2. The within-host model describes the equations involved in the life cycle of SARS-CoV-2, and also the immune response; while that the between-Host model analyzes the dynamics of virus spread from the original source of contagion associated with bats, subsequently transmitted to a host, and then reaching the reservoir (Huanan Seafood Wholesale Market in Wuhan ), until finally infecting the human population.
Keywords: Covid-19; Origin; Hosts; Reservoir; Immune; Transmission model; SARS-CoV-2 .